Case report of cyclopia baby - A rare lethal anomaly (Indian Journal of Case Reports, 2018)
Cyclopia is a rare and lethal human malformation, with a single eye in the center of the forehead. We report the case of a woman aged 23 years (second gravida) referred to us at 30 weeks of pregnancy and delivered a stillborn weighing 1.02 kg. The baby had a single central eye, low set ears, omphalocele, and single umbilical artery. With advances in fetal imaging and availability of high-resolution ultrasound machines, it is surprising that such lethal malformations are still presenting after the period of viability. To reduce such incidences, more awareness and emphasis must be made out on early ultrasound diagnosis of fetal anomalies and regular antenatal visits.